2010
DOI: 10.1271/bbb.90736
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Components and Synthesis Genes of Cell Wall Teichoic Acid amongLactobacillus plantarumStrains

Abstract: The contents, components, and synthesis genes of cell wall teichoic acid (WTA) in 18 strains of Lactobacillus plantarum were compared. The WTA of each strain was classified by its components as being either the glycerol- or the ribitol-type. The different strains in the WTA type showed marked differences also in two gene regions, tagD1-tagF2 and lp_1816-tagB2, as for the presence or absence, nucleotide sequences, and transcriptional activities. Our results clearly showed that the tagD1-tagF2 and lp_1816-tagB2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…Among lactobacilli, wall teichoic acids (WTA) ultrastructures of L. plantarum are the most studied. It is known that L. plantarum is the only lactobacilli species which can contain either polyribitolphosphate or polyglycerophosphate in its WTA [15,17]. Our data showed the presence of polyglycerophosphate in WTA of the tested strains.…”
Section: Discusionsupporting
confidence: 52%
See 2 more Smart Citations
“…Among lactobacilli, wall teichoic acids (WTA) ultrastructures of L. plantarum are the most studied. It is known that L. plantarum is the only lactobacilli species which can contain either polyribitolphosphate or polyglycerophosphate in its WTA [15,17]. Our data showed the presence of polyglycerophosphate in WTA of the tested strains.…”
Section: Discusionsupporting
confidence: 52%
“…The glycosyl residues of teichoic acids are commonly represented by multiple glucose residues in a range of configurations [15], but usually no more 1 or 2 kinds per molecule [5,6,11]. However our study revealed the presence of unusually high number of sugar units (up to 9).…”
Section: Discusionmentioning
confidence: 54%
See 1 more Smart Citation
“…Lactobacillus fermentum, Lactobacillus casei, Lactobacillus reuteri and Lactobacillus rhamnosus (Kleerebezem et al, 2010;Bron et al, 2012b). Intriguingly, Lactobacillus plantarum appears to be unique in its capacity to produce either Gro-or Rbocontaining WTA in the cell wall (Tomita et al, 2010). Previous WTA studies in different Lb.…”
Section: Introductionmentioning
confidence: 99%
“…The Gro-or Rbo-WTA production in Lb. plantarum depends on two distinct genetic clusters harbouring tag or tar genes (Tomita et al, 2010). The cluster encoding tagD1-tagF1-tagF2 (the tag locus) is only present in Gro-WTA-producing strains and absent in the Rbo-WTA-producing strains, and determines the Gro-WTA phenotype.…”
Section: Introductionmentioning
confidence: 99%